A Study on the Perception of Climate Change and its Awareness Level Among the Students in UTHM Pagoh Campus - RAJADURAI, KESHANA; Abdul Wahid, Abdul Zaki (Progress in Engineering Application and Technology, 2023)
Climate change refers to long-term shifts in temperatures and weather patterns. Since the industrial revolution, human emissions of greenhouse gases from fossil fuel combustion, deforestation, and agricultural practices have led to climate change occur. Therefore, the purpose of this research is to explore the consumer perception of climate change among UTHM Pagoh students. The first objective is to identify the relationship between consumer perception and climate change and the second objective is to analyse the level of awareness of the consumer on climate change. This study was conducted using a questionnaire instrument. The questionnaire was distributed in google form to 341 respondents. The data were collected and analysed using the Statistical Packages for Social Science (SPSS) Version 26 software. Data will be calculated using the descriptive analysis method to obtain the frequency, percentage and mean score. The results of the study show that the frequency of respondents’ answers for knowledge and understanding of consumer regarding climate change among consumers of UTHM Pagoh students is at a high level. Meanwhile, the mean level interpretation results for awareness of consumers on climate change are at a high level however, the results for behavior and attitude of consumers on climate change are at a moderate level. Therefore, the findings of the study show that consumers are aware of the causes of climate change but they are not contributing their part in how to reduce the effect of climate change in their daily life. This study is expected to provide input and help the consumer in raising awareness about climate change.